Resilience of Vocational High School Students from Divorced Families: Facing Challenges and Navigating Career Choices - Puspitasari, Desty Ratih; Nurhadi, Didik; Yoto, Yoto (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to investigate the resilience of vocational high school students from divorced families as they encounter life challenges and make career decisions. Employing a qualitative intrinsic case study approach, the research involved students from divorced families as the main participants. Data were collected through in-depth interviews with participants and their significant others, supported by document analysis, and analyzed using a thematic analysis approach. The results reveal five key themes: parental divorce, coping dynamics, sources of resilience, career choices, and factors influencing career decisions. The findings indicate that resilience is influenced by emotional regulation, stress-coping strategies, attachment figures, self-control, gratitude, and optimism dimensions that correspond to the concepts of